Sub-5-fs laser-driven nanophotonics in the relativistic intensity regime - Veisz, L.; Cardenas, D. E.; Lucchio, L. Di; Ostermayr, T.; Hofmann, L.; Kling, Matthias Friedrich; Schreiber, J.; Gibbon, P. (Optics InfoBase Conference Papers, 2018)
We investigated the interaction of nanometric tungsten targets with ultra-relativisticintensity sub-5-fs laser pulses. Electrons accelerated to multi-MeV energy with electric fields exceeding the TV/m range and dependence on the laser waveform (carrier-envelope phase) were observed.
CRIS-Team Scopus Importer:2023-04-20